Romania : Energy Sector Rapid Assessment - World Bank (Washington, DC, 2014)
The energy sector rapid assessment was conducted by the World Bank for the Government of Romania, as part of an advisory services program on climate change and low carbon green growth. The objective of this assessment is to identify climate change related investment priorities and necessary implementation support for the 2014-2020 operational programs, with a view to achieving the European Union (EU) 2020 targets and laying a foundation for continued de-carbonization of the energy sector. This rapid assessment focuses on climate change mitigation actions in power and heat generation and in energy use in manufacturing, residential, public, and commercial sectors. Energy use and efficiency in the transport sector is studied in a separate transport sector rapid assessment. It includes in-depth investigation of the main energy end-use sectors or subsectors, low-carbon energy supply optimization based on long-term energy demand patterns and trends, and the design and approaches of key energy efficiency intervention programs, such as thermal retrofit of residential and public buildings and economization and modernization of district heating systems.